Helicobacter pylori World Gastroenterology Organization Global Guideline. Issue 2 (15th February 2023) - Katelaris, Peter; Hunt, Richard; Bazzoli, Franco; Cohen, Henry; Fock, Kwong Ming; Gemilyan, Manik; Malfertheiner, Peter; Mégraud, Francis; Piscoya, Alejandro; Quach, Duc; Vakil, Nimish; Vaz Coelho, Louis G.; et al.
Abstract : Helicobacter pylori remains a major health problem worldwide, causing considerable morbidity and mortality due to peptic ulcer disease and gastric cancer. The burden of disease falls disproportionally on less well-resourced populations. As with most infectious diseases, the largest impact on reducing this burden comes from improvement in socioeconomic status, which interrupts transmission. This has been observed in many regions of the world, but the prevalence of infection remains high in many regions where improvements in living standards are slow to occur. Meanwhile, the optimal clinical management and treatment pathways remain unsettled and are evolving with changing antimicrobial resistance patterns. Despite decades of research and clinical practice, major challenges remain. The quest for the most effective, safe, and simple therapy remains the major issue for clinicians. The search for an effective vaccine appears to be elusive still. Clinical guidelines do not infrequently proffer discordant advice. A major challenge for guidelines is for relevance across a variety of populations with a varying spectrum of disease, antimicrobial resistance rates, and vastly different resources. As local factors are central to determining the impact and management strategies for H. pylori infection, it is important that pathways are based on the best available local knowledge rather than solely extrapolating from guidelines formulated in other regions, which may be less applicable. To this end, this revision of the World Gastroenterology Organisation (WGO) H. pylori guideline uses a "Cascades" approach that seeks to summarize the principles of management and offer advice for pragmatic, relevant and achievable diagnostic and treatment pathways based on established key treatment principles and using local knowledge and available resources to guide regional practice.